Application of Sampling Plan Methods: Case of Indonesian Sugar Company - Suwondo, Endy; Yuliando, Henry; Guritno, Adi Djoko (2014)
A study of sampling plan for controling the quality of bags in a sugar company has been done. The data was taken from 25 random samples for several methods applied including Variable Single Sampling, Quality Index Sampling, and Attribute Proportion Sampling. It was found that the best sampling method is Variable Single Sampling, that gives significant result for all tested parameter and offer an efficient way for the company in doing the inspection and quality control.